Mindray Anesthesia Machine Repair Type Wato Ex-65 at Columbia Asia Special Surgery Hospital Semarang - Andy Setiawan; Pramesti Kusumaningtyas; Bayu Wahyudi (Journal of Engineering, Electrical and Informatics, 2025)
Anesthesia machines are very important medical equipment in modern medicine, especially in medical procedures and intensive care. This device is designed to provide and control the administration of anesthetic drugs and medical gases to patients safely and accurately. Damage to the oxygen regulator block of the anesthesia machine shows a discrepancy with the indicator reading. This problem is very critical because it can cause the administration of inappropriate oxygen concentrations to patients during anesthesia procedures. This activity aims to support health services at the Columbia Asia Semarang Hospital which has a damaged anesthesia machine and wants to be repaired, namely the Mindray Type Wato EX-65 anesthesia machine. Damage to the device is known by disassembling the device, by visual observation, checking for hose leaks, and measuring at certain points in the device circuit. Based on the analysis carried out, the damage is in the anesthesia machine regulator block. After repairs and functional tests using VT 305 to check the air flow, it was declared suitable for use.